Upaya Pencegahan Dampak Kemelut Rumah Tangga Melalui Program Pendidikan Pranikah Bagi Pemuda-Pemudi Muslim Kota Medan - Rahmat Rifai Lubis; Ahmad Sukri Harahap (Hikmah, 2017)
This research aims to: (1) Establish a youth of Muslim Village Binjai, sub-district of Medan Denai in order to have a personality that is knowledgeable, skilled and have the readiness to undergo marriage, (2) Establish a social sensitivities household conditions are not harmonized, (3) Deter and minimize the impact of domestic brawl occurred among Muslims, especially in Village Binjai, sub-district of Medan Denai. The method used in this study is a case-based reasoning (CBR). This method emphasizes problem solving based on knowledge of previous cases. The results showed an increase in program participants' understanding of marriage. From that initially only 19 people only considered to have knowledge about the wedding, rose to 61 people. The results also show high social sensitivity of participants to the dangers of the impact of domestic brawl, it was consummated by the formation of premarital education community.